A study on the bridge of music intelligence to Chinese comprehension: Hope and limitation? - Liu, Wei-Yu (Advances in Social Sciences Research Journal, 2020)
This study aims to use the theory of multiple intelligences to explore the strategies of music intelligence bridging Chinese comprehension and their impacts on students’ learning. An action research was conducted since the purposes of this study are both to test multiple intelligences theory and to improve Chinese teaching. Several models and approaches have been developed to apply multiple intelligences theory into practice in K-8 classrooms. Baum et al (2005) identified five pathways to apply multiple intelligences theory in the elementary classroom; they are Explorations, Building on Strengths, Understanding, Authentic Problems, and Talent Development. While Viens and Kallenbach (2004) labeled the first fourth as MI Reflections, Bridging Students’ Areas of Strengths to Areas of Challenge, Entry/Exit Points, and Projects. The approach of Bridging Students’ Areas of Strengths to Areas of Challenge is to create a "bridge" from students’ MI strengths to appropriate learning strategies, emphasizing using students’ particular strengths to assist in areas of particular difficulty (Viens & Kallenbach, 2004). The models of Vocabulary-in-Song bridging Chinese reading comprehension was built and discussed. Teaching skills which must be coupled with the bridging model were discussed. The hope and limitation of Vocabulary-in-Song bridging Chinese reading comprehension were showed.